BRIEF REVIEW OF N-ACETYLCYSTEINE AS ANTIVIRAL AGENT: POTENTIAL APPLICATION IN COVID-19: Use of N-Acetylcysteine as Antiviral Agent - Ervilla Dass (Journal of Biomedical and Pharmaceutical Research, 2020)
Novel Coronavirus disease 2019 – COVID-19, was first identified amongst an outbreak of respiratory illness cases in Wuhan City, Hubei Province, China. Research for effective therapies including antiviral agents, immunotherapies, and vaccines are being investigated and developed as potential therapies. Acetylcysteine a precursor in the formation of the antioxidant Glutathione (GSH) in the body is an important determinant of cellular redox status in endothelial cells, in maintaining intracellular GSH/Glutathione oxidized (GSSG) homeostasis, hence represents one of the most important antioxidant defense systems in lung cells, also, used in the prophylaxis or therapy of Virus Diseases. There are multiple reasons for maintaining adequate GSH levels in lungs. Researchers have demonstrated that, immunomodulatory agents that have increased survival in combination with influenza antivirals in murine models include N-acetylcysteine. These anti-oxidant capacities of NAC are mostly indirect, via a pro-glutathione effect where NAC provides L-cysteine residues required for glutathione synthesis. Therefore, antioxidants like NAC represent a potential additional treatment option that could be considered either as adjuvant therapy. According to the latest study by Jason Kim et al, March 2020, it is indicated glutathione, as top hits and highly ranked for potential benefit against SARS-CoV-2; and have also warranted further investigation for potential benefit against SARS-CoV-2. Still, its clinical effectiveness needs further investigations, since most of the results in this area of research are derived from in vitro and in vivo studies. Further research as antiviral agent may provide a new therapeutic strategy for the treatment of viral infections such as COVID 19. Keywords: COVID-19, World Health Organization (WHO), N-Acetylcysteine, Antiviral, reactive oxygen intermediates, glutathione, antioxidant